An X-ray investigation of the adsorption of methane, water, and their mixtures in carbon micropores. (April 2015) - Futamura, Ryusuke; Ozeki, Sumio; Iiyama, Taku
Abstract: The adsorption of methane and water, and their coexisting state in carbon micropores were investigated by X-ray scattering measurements. The mechanisms of single-component adsorption of water and methane in the carbon micropores proceeded by cluster formation and micropore filling, respectively. The X-ray scattering of the coexisting state reveals that a mesoscopic phase separation occurred in the carbon micropores at 111 K because of the weak interaction between water and methane. At this low temperature, water molecules could not reform hydrogen bonds even with further adsorption of methane molecules. The X-ray scattering measurements provided detailed information on the coexisting state and can be used to study the temperature dependence of the phase behavior of the methane–water system during methane hydration formation in nanospaces.